Cost-effectiveness analysis of sorafenib, lenvatinib, atezolizumab plus bevacizumab and sintilimab plus bevacizumab for the treatment of advanced hepatocellular carcinoma in China - Hongyu Gong; Siew Chin Ong; Fan Li; Zhiying Weng; Keying Zhao; Zhengyou Jiang (Cost Effectiveness and Resource Allocation, 2023)
Key points With the approval of new first-and second-line drugs and the establishment of treatment based on immune checkpoint inhibitors as standard treatment, treatment options for advanced hepatocellular carcinoma are more diverse than ever before. Therefore, clinical decision-making requires a multidisciplinary team to develop individualized treatment strategies according to the patients' disease and financial ability to pay. Here, we point out that lenvatinib, sintilimab plus bevacizumab and atezolizumab plus bevacizumab are more effective in the treatment of advanced hepatocellular carcinoma, but the cost of treatment is beyond the affordability of the patient. We outlined better drug purchase prices and health insurance reimbursement policies to enable patients to get the optimal treatment.